2020
DOI: 10.31571/bahasa.v9i1.1681
|View full text |Cite
|
Sign up to set email alerts
|

Transitivity Analysis of Students’ Recount Texts

Abstract: <p>This study aimed at identifying the process types that characterize the students’ recount texts, identifying the process types which are dominantly used, and identifying the circumstantial elements that characterize the students’ recount texts. This study applied a descriptive qualitative method with a case study research. The recount texts written by class XI <em>Usaha Perjalanan Wisata</em><em> (UPW)</em> 2 at SMK Wira Harapan were used as the sources of data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…Besides, as the texts were written by professional textbook writers, the ones composed by students depicted the similar findings as the final analysis of the recount text that students finalized; in fact, this study came to the connclusion that material was the most process type as students produces recount texts (Elsie, Adnyani, & Suarnajaya, 2020). Despite divergent written with wide different skills, knowledge and writing experience, the same genre of text written by anyone regardless of their background generate typical identical process types.…”
Section: Table 4 Subject-object In Narrative Textssupporting
confidence: 53%
“…Besides, as the texts were written by professional textbook writers, the ones composed by students depicted the similar findings as the final analysis of the recount text that students finalized; in fact, this study came to the connclusion that material was the most process type as students produces recount texts (Elsie, Adnyani, & Suarnajaya, 2020). Despite divergent written with wide different skills, knowledge and writing experience, the same genre of text written by anyone regardless of their background generate typical identical process types.…”
Section: Table 4 Subject-object In Narrative Textssupporting
confidence: 53%
“…Research regarding the implementation of transitivity in students' recount texts has been done before. Research done by (Elsie et al, 2020;Fajriah, 2021;Novianto et al, 2022;Rahayu & Efransyah, 2020;Rahmawati, 2019;Rosmayanti et al, 2021;Utami et al, 2022) revealed that the most prevalent material process found in the data for students' recount text was retelling something that happened in the past that the students experienced. This article will concentrate on the transitivity of students' writing recounts with quantitative and qualitative methods.…”
Section: Introductionmentioning
confidence: 99%